2021
DOI: 10.5306/wjco.v12.i6.437
|View full text |Cite
|
Sign up to set email alerts
|

Imaging diagnosis of bronchogenic carcinoma (the forgotten disease) during times of COVID-19 pandemic: Current and future perspectives

Abstract: Patients with bronchogenic carcinoma comprise a high-risk group for coronavirus disease 2019 (COVID-19), pneumonia and related complications. Symptoms of COVID-19 related pulmonary syndrome may be similar to deteriorating symptoms encountered during bronchogenic carcinoma progression. These resemblances add further complexity for imaging assessment of bronchogenic carcinoma. Similarities between clinical and imaging findings can pose a major challenge to clinicians in distinguishing COVID-19 super-infection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In the past three years, novel coronavirus (COVID-19) pneumonia infection has affected almost everyone and has had a huge impact on the treatment of patients with malignancy. Pinato D J et al (68) described factors associated with the development of sequelae in COVID-19 surviving oncology patients and their relationship with survival after infection, and found that 15.0% of patients had at least one COVID-19 sequelae at the time of first oncology reassessment, including 116 (49.6%) respiratory sequelae, such as chronic cough, residual dyspnea, and shortness of breath, which undoubtedly caused irreversible damage, and residual inflammatory and interstitial fibrotic lung changes are more likely to lead to CIP, while the symptoms of COVID-19related pulmonary syndrome may be similar to the worsening of symptoms encountered during lung cancer progression (69). The similarity of clinical and imaging findings poses a greater challenge for confirmatory evaluation, and distinguishing whether the development of pneumonia is associated with ICIs becomes more important.…”
Section: Infectionmentioning
confidence: 99%
“…In the past three years, novel coronavirus (COVID-19) pneumonia infection has affected almost everyone and has had a huge impact on the treatment of patients with malignancy. Pinato D J et al (68) described factors associated with the development of sequelae in COVID-19 surviving oncology patients and their relationship with survival after infection, and found that 15.0% of patients had at least one COVID-19 sequelae at the time of first oncology reassessment, including 116 (49.6%) respiratory sequelae, such as chronic cough, residual dyspnea, and shortness of breath, which undoubtedly caused irreversible damage, and residual inflammatory and interstitial fibrotic lung changes are more likely to lead to CIP, while the symptoms of COVID-19related pulmonary syndrome may be similar to the worsening of symptoms encountered during lung cancer progression (69). The similarity of clinical and imaging findings poses a greater challenge for confirmatory evaluation, and distinguishing whether the development of pneumonia is associated with ICIs becomes more important.…”
Section: Infectionmentioning
confidence: 99%